Conservative treatment of recurrent temporomandibular joint dislocation with autologous blood injection (Annals of Medical Research, 2021)
Aim: Temporomandibular joint (TMJ) dislocation is very distressing condition and is common in society. TMJ may be treated by conservative methods but the cases with persistent may require surgical.Autologous blood injection(ABI) to TMJ is a nonsurgical method provides more effective outcomes compared to other methods and has been long studied in the literature. ABI is based on the injection of the blood drawn from the antecubital fossa into the superior joint space. The inflammatory changes develop in the joint and maturation of blood after the administration of ABI limit the mandibular movements.Eminectomy seems to provide a permanent solution for the surgical treatment of TMJ, it is a risky method since the mandibular area is neighbored by critical anatomical structures.Therefore conservative methods should be tried before initiating advanced surgical techniques.
Keywords: Autologous blood injection; Temporomandibular Joint; Chronic Dislocation.